Teaching Spanish Pragmatics Through Colloquial Conversations - Albelda Marco, Marta (marcoELE. Revista de Didáctica Español Lengua Extranjera, 2017)
This paper focuses on the advantages of teaching and learning a foreign language with and through spoken discursive corpora, and especially colloquial and conversational ones. The benefits of developing oral competence and communicative skills in language learners using colloquial conversations will be exposed and discussed. In this paper, we characterise the colloquial conversation and the features that define this register and discursive genre. Being the most natural and original way to communicate among human beings, the colloquial conversation is the most common means to communicate, and therefore, this genre should have a greater presence in foreign-language classrooms. Secondly, we expound on the advantages of teaching using colloquial conversations corpora, particularly resulting from its contextualisation (the linguistic input is learnt in its real and authentic context) and from its oral and conversational features (prosodic elements and interactional mechanisms). Thirdly, the paper provides a list of corpora of colloquial conversations that are available in Spanish, focusing on Val.Es.Co. colloquial corpus (peninsular Spanish oral corpus, Briz et al., 2002; Cabedo & Pons online, www.valesco.es). Finally, a set of pragmatic applications of corpora in foreign-language classroom is offered, in particular using the Val.Es.Co. colloquial corpus: functions of discourse markers and interjections (whose meanings change depending on the context), strategies of turn-takings, ways of introducing new topic in the dialogues, mechanisms of keeping or “stealing” the turn, devices to introduce direct speech, attitudes expressed by the falling and rising intonations, hedges and intensifiers, and so on. In general, this paper pretends to offer ideas, resources and materials to make the students more competent in communication using authentic discursive oral corpora.